Reading the footprints: How foreign investors shape countries' participation in global value chains - Christian Buelens; Marcel Tirpák (European Central Bank (ECB), 2017)
We show that traditional gravity variables play a significant role in explaining trade flows related to global value chain participation. We find evidence that cooperation costs - measured by linguistic and geographical proximity - are more relevant for trade that reflects cross-border production sharing. Applying an augmented gravity model framework to a newly-constructed dataset we find a positive association between bilateral FDI stock and both gross bilateral trade and the bilateral import-content of exports. We confirm this finding using an empirical case study on central and eastern European countries, which from a global perspective stand out both in terms of degree of global value chain-participation and size of inward FDI stock. Overall, we show that foreign investors play an active role in shaping host economies' export structure and their participation in international production networks. Policies that attract foreign direct investment would therefore constitute an indirect way to deepen a GVC-participation.
Keywords: F14; F15; F21; L22; 330; global value chains; value added trade; foreign direct investment; gravity model